Study on the damage evolutional process of secondary tunnel lining under rheological effect of surrounding rock. (December 2022) - Xu, Guowen; Wang, Bo; Ma, Gaoyu; Du, Jiamin; Chen, Xu; Hou, Zhenkun
Highlights: A simplified method is adopted in the model test to simulate the creep effect of rocks. The cracking and failure process of lining is investigated in the model test. The damage process of lining under creep effect of rock is studied through numerical simulation. Abstract: Cracks are prone to occur in the secondary tunnel lining with the action of rheological deformation of surrounding rock, which will cause severely structural defects and adversely affect the long-term safety of tunnels. In this article, similar model tests and numerical simulations were conducted to investigate this issue. First, the overloading method was adopted as a simplified way to investigate the failure evolution process of lining in the model test. Then, the long-term safety of lining under the influence of geo-stress field, the amount and location of voids were revealed through numerical simulations. The results show that: (1) The variation of inner force with loading steps has two distinct stages that are similar to those for lining under the creep effect of rocks, which validates the availability of the overloading method preliminarily. (2) Sections of lining near the void bend outward, and the axial force in these sections is smaller than that of the other sections. (3) The failure process for lining with no void shows evidently progressive feature with the occurrence of two stress adjustment processes before its failure, while the existence of void accelerates the failure process of lining. (4) A crack near the void appears in the lining when the lining reaches its ultimate limit state of carrying capacity, and the crack occurs earliest compared to other cracks.